2019
DOI: 10.1200/jco.19.00555
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Trial of Chemotherapy With or Without Bevacizumab in Patients With Recurrent or Metastatic Head and Neck Cancer

Abstract: PURPOSE We evaluated the addition of bevacizumab, a humanized monoclonal antibody that targets vascular endothelial growth factor, to platinum-based chemotherapy in recurrent or metastatic squamous cell carcinoma of the head and neck (SCCHN). PATIENTS AND METHODS Patients with chemotherapy-naïve (or with prior platinum as part of multimodal therapy completed ≥ 4 months earlier) recurrent or metastatic SCCHN were randomly assigned to receive a platinum-based chemotherapy doublet with or without bevacizumab 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 12 publications
0
89
1
Order By: Relevance
“…In total, 431 studies were identified through database search and 186 additional studies were identified through trial registers, international conferences, references of reviews, and other sources. Twenty RCTs 5 7 , 10 , 19 34 with full texts and six with abstracts only 9 , 35 – 39 met the eligibility for assessment ( Figure 1 ). The amount of evidence included is illustrated using a network diagram ( Figure 2A , 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 431 studies were identified through database search and 186 additional studies were identified through trial registers, international conferences, references of reviews, and other sources. Twenty RCTs 5 7 , 10 , 19 34 with full texts and six with abstracts only 9 , 35 – 39 met the eligibility for assessment ( Figure 1 ). The amount of evidence included is illustrated using a network diagram ( Figure 2A , 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…metastatic SCC of the head and neck, did not demonstrate efficacy in increasing overall survival but improved the response rate and progression-free survival [24]. These results encourage further biomarker-driven studies to identify other more effective angiogenesis inhibitors.…”
Section: Plos Onementioning
confidence: 89%
“…The results of meta-analysis that included 12 studies comprising 1002 patients showed that overexpression of VEGF receptor (VEGFR) in 90% of head and neck squamous cell carcinomas (SCC) and the up-regulation of VEGFR was associated with poorer survival outcomes [ 23 ]. However the results of currently performed trials analyzing the addition of bevacizumab, a monoclonal antibody targeting VEGF, to platinum-based chemotherapy in recurrent or metastatic SCC of the head and neck, did not demonstrate efficacy in increasing overall survival but improved the response rate and progression-free survival [ 24 ]. These results encourage further biomarker-driven studies to identify other more effective angiogenesis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase III clinical trial which evaluated the addition of bevacizumab to platinum-based chemotherapy in recurrent or metastatic SCCHN, showed that the addition of bevacizumab did not improve overall survival but did improve response rate and progression-free survival. Nevertheless, there was a significant increase in toxicity, including bleeding events and treatment related deaths [ 79 ].…”
Section: Oral Cancermentioning
confidence: 99%